Sejarah Perkembangan dan Kemunduran 3 Kerajaan Islam di Abad Modern (1700-1800an) - Kartini, Kartini; M, M. Dahlan; Rahmawati, Rahmawati (Indo-MathEdu Intellectuals Journal, 2024)
This article aims to find out the history of the development of the three great Islamic kingdoms in the Middle Ages. This article uses a qualitative approach with the literature study method. This method is intended to examine various sources relevant to the focus of this research. The main sources of research data are scientific books and articles published in various scientific journals and indexed on the google scholar database. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. Research findings show that three important Islamic empires were created in the late 15th and early 16th centuries: the Ottoman Empire in Turkey, the Mughal Empire in India, and the Safavid Empire in Persia. The three important Kingdoms seem to focus their sights more on the democratic tradition of Islam and build an absolute empire. Almost every aspect of general life was carried out with systematic and bureaucratic precision and various kingdoms developed an elaborate administration. These three great kingdoms seemed to revive the glory of Islam after the collapse of the Abbasids. However, the progress made during the three great kingdoms is different from the progress made during the classical Islamic period